An anatomization of concrete elements with Taguchi optimization method. (2021) - Sabarish, K.V.; Parvati, T.S.
Abstract: In this modern construction world, the infrastructural development in the concrete plays a pivotal role. Due to huge demand in the concrete ingredients such as cement which act as binding materials, fine aggregates and coarse aggregates which act as filling materials in the concrete, the material price has been increasing. In this manuscript, the analysis on Flexural and Saturation water absorption test with concrete elements, with conjunctions of various substitutes for concrete materials like fly-ash, M−sand and additive sisal fibre. To minimize the overutilization of concrete materials, the optimization method is incorporated to diminish the total volume of materials required for concreting. This paper focusing on the Taguchi optimization method with L9 orthogonal array to identify the most optimum combination for the best results with minimum resources and the impact of each parameter are identified by sound-to-noise ratio. The Grey relational analysis (GRA) is also identified to cross examine the Taguchi optimized responses. The ANOVA is used in the experimental variances to analyse its range of acceptances.